Efeito de biomateriais no crescimento e funcionalidade de células progenitoras da polpa dentária - Bin, Claudia Villela [UNESP] (2014)
With the use of principles of regenerative therapies in Endodontics, new tissue engineering strategies have showed success in the de novo formation of pulp tissue in animal models. The commonly used materials on the original dental pulp tissue are the MTA and calcium hydroxide. In addition, a new material known as Biodentine, based on tricalcium silicate, is new to the market, with the same purpose of the others. However, the biological effects and mechanisms of this bioactive material are not elucidated. This project evaluated the effects of these biomaterials on dental pulp stem cells. The biocompatibility of them was assessed by XTT and SRB assays, at 1, 3 and 5 days. The alkaline phosphatase activity assay and alizarin red staining of mineralized nodules was assessed by functional mineralization. The results were subjected to statistical analysis (ANOVA and Tukey 5%) and demonstrated a significant Biodentine's biocompatibility in cytotoxicity assays. However, Ca(OH)2 cement was the material that was most stimulated ALP activity. In addition, all cements enabled the formation of mineralized nodules from the seventh day, in alizarin red test